Nanoscale stress distributions and microstructural changes at scratch track cross-sections of a deformed brittle-ductile CrN-Cr bilayer. (October 2020) - Meindlhumer, M.; Zalesak, J.; Ecker, W.; Rosenthal, M.; Niese, S.; Gawlitza, P.; Hruby, H.; Mitterer, C.; Daniel, R.; Keckes, J.; Todt, J.
Abstract: In order to interpret the mechanical response of thin films subjected to scratch tests, it is necessary to elucidate local stress distributions and microstructural changes accompanying deformation across the scratch track area. Here, 50 nm synchrotron cross-sectional X-ray nanodiffraction and electron microscopy are used to characterize nanoscale multiaxial residual stress gradients and irreversible microstructural-morphological changes across a brittle-ductile film consisting of 1.2 and 2 μm thick CrN and Cr sublayers. The experimental results reveal a complex alternation of the original columnar grain microstructure and a formation of pronounced lateral and depth stress gradients, which are complemented by a finite element model. After scratching, steep gradients of in-plane, out-of-plane and shear stress distributions were revealed, ranging from −6 to 1.5 and − 1.5 to 1.5 GPa in CrN and Cr, respectively, which are furthermore correlated with microstructural changes and residual curvatures. The scratch test results in intergranular grain sliding and the formation of nanoscopic intragranular defects within CrN, while Cr sublayer's thickness reduction and pile-up formation are accompanied by a bending of columnar crystallites and localized plastic deformation. In summary, the quantitative stress data elucidate the stabilizing role of the Cr sublayer, which suppresses the bilayer's catastrophic fracture during scratch tests. Graphical abstract: Unlabelled Image Highlights: Experimentally determined multi-axial residual stress distributions across a scratched Cr-CrN bilayer film reveal deformation mechanisms. The ductile Cr sublayer provides toughening through plastic deformation while the hard/brittle CrN toplayer absorbs severe stresses, functioning synergistically. Small-angle X-ray scattering and X-ray peak width analyses elucidate microstructural changes unaccounted for by finite element modelling.